Adjustment of In-Depth Interview and Focus Group Discussion Guidelines for Disaster Victims Evacuation Model Development with Corona Virus Disease 2019 Pandemic - Muhammad, Muhammad; Kamil, Hajjul; Adlim, Adlim; Irwandi, Irwandi (International Conference on Multidisciplinary Research, 2021)
In developing the disaster victim evacuation (DVE) model, we started with exploratory study is needed to identify the related variables. The exploratory studies are in the form of qualitative and quantitative research. In this qualitative study conducted agent-based in the nursing perspective. To conduct this research, guidelines are needed that are in accordance with the actual situation, such as the global COVID-19 pandemic. Although many articles have been published regarding in-depth interview (II) and Focus Group Discussion (FGD) guidelines, all of them have to be readjusted according to the situation. This adjustment is important to do minimize problems that arise in the data collection process, such as the emergence of new clusters during pandemic of the Covid 19. This study aims to provide a detailed standard in the implementation of the data collection process using the II & FGD method for the DVE Model development and in accordance with pandemic conditions.This literature review study begins with article search and identification of scientific articles. Before the scientific articles are synthesized, a variable identification process is carried out through 2 stages, namely identification to sort articles according to variables and article selection for research main reference needs and references for discussion.. The results of this study are in the form of qualitative research guidelines presented in the form of standard data collection methods using II & FGD. In this article, we recommend aligning the II & FGD guidelines with the development of information technology in exploring Agent-based information. Keywords: In-depth Interview, FGD, disaster & Model